2006
DOI: 10.1001/archpedi.160.6.610
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Compensation Behavior in Children

Abstract: Results of this study provide no support for hypotheses about risk homeostasis theory among children using PE. The validity of the theory appears highly doubtful for children in this age range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…One important limitation of the studies by both researchers is that most are laboratory based and thus inconclusive with respect to their real-life implications. In contrast, another study based on actual interviews following an injury, provides no support for RCT [24].…”
Section: Child-related Examplesmentioning
confidence: 94%
“…One important limitation of the studies by both researchers is that most are laboratory based and thus inconclusive with respect to their real-life implications. In contrast, another study based on actual interviews following an injury, provides no support for RCT [24].…”
Section: Child-related Examplesmentioning
confidence: 94%
“…This theory, which was popularized by Wilde, 90 has obvious implications for sportinjury prevention, particularly for the development of protective equipment. Although there is no empirical evidence that risk compensation affects injury rates with protective equipment use in intercollegiate ice hockey, 91 skiing and snowboarding, 92 or other children's activities, 93 there is some evidence for reported behavior change with protective-equipment use in children's activities. 94 In fact, a recent study revealed that children reacted to wearing safety gear by showing both greater speed and increased recklessness in behavior.…”
Section: Who Should Be Responsible For the Prevention Of Injury In Yomentioning
confidence: 99%
“…Using disposition as a general proxy of injury severity, 28 these data demonstrate that most ED patients received treatment for their alcohol-related injuries and this proportion increased with age (Fig. 2).…”
Section: ; 11 (4) 333mentioning
confidence: 88%
“…35 Nonetheless, past CHIRPP studies 28,35 have found the data to be of high quality, with only minor systematic errors in data capture. Despite these recognized limitations, the CHIRPP data set offers a novel look at alcohol-related injury patterns, and, if anything, provides a conservative estimate of the burden of alcoholrelated injury among Canadian youth.…”
Section: Limitationsmentioning
confidence: 99%